Feasibility study of intravascular pulsed electric field ablation for the treatment of cardiac arrhythmias - Wang, Zhen; Li, Yunhao; Liang, Ming; Sun, Jingyang; Zhang, Jie; Xu, Lisheng; Han, Yaling (Frontiers in Physiology, 2025)
BackgroundPulsed electric field ablation (PFA) techniques for treating cardiac arrhythmias have attracted considerable interest. For example, atrial fibrillation can be effectively treated by pulmonary vein isolation using PFA. However, some arrhythmias originate deep within the myocardium, making them difficult to reach with conventional ablation methods. Therefore, this study aimed to explore endovascular catheter-based ablation using computational modeling to assess the electric field and temperature distributions during the procedure.MethodsA three-dimensional computer model of the ablation catheter and heart was developed. The catheter was positioned within the heart model to simulate endovascular ablation, and the ablation damage range was estimated using the 1000 V/cm contour. Additionally, a probe function was used to monitor the maximum electric field and temperature within the ablation zone to evaluate the feasibility and safety of this approach.ResultsThe electric field can penetrate blood vessels and fat to induce effective myocardial injury. The extent of myocardial damage increases with higher pulse voltages; however, excessive voltage may also damage blood vessels (vascular damage threshold: 3500 V/cm). An appropriate electrode configuration can achieve a more uniform myocardial injury across different cross-sections. Temperature rise near the catheter electrode is significant, but appropriate pulse interval settings can prevent thermal damage in the target area (simulated maximum temperature: 46.8 °C; thermal damage threshold for biological tissue: 55 °C).ConclusionIntravascular pulsed electric field ablation can effectively damage the myocardium without harming blood vessels when suitable pulse parameters are applied. The ablation device settings strongly influence the maximum temperature in the ablation zone and help limit thermal effects. These findings support the feasibility of using small endovascular catheters to treat cardiac arrhythmias.